Does regulation affect market power? Evidence from Greek SMEs - Michael L. Polemis; Aikaterina Oikonomou (SPOUDAI - Journal of Economics and Business, 2016)
The aim of this study is to examine the level of market power of the Greek Small and Medium-sized Enterprises (SMEs) acting in the manufacturing and services industries respectively. This has been performed at a two digit level over the period 1970-2007, with the aim of investigating possible heterogeneity across different subsectors of the above industries. The results of our analysis are linked with a number of interesting implications for the competition authorities. First, mark-ups can provide valuable information on competitive pressures in various sectors of the Greek economy, reflecting pressures stemming from rules of conduct imposed by regulators as well. Second, the estimation of mark-up ratios may benefit policy makers and government officials to pursue pro-competitive regulatory reforms in order to maximize consumer surplus. Third, the regulators may examine if market power changes over time and assess the effectiveness of deregulation on it. Lastly, the empirical findings indicate that there is a negative relationship between mark-ups and regulation taken one-period back. In other words, we claim that the level of regulatory reform affect the level of market power one-period ahead and cannot explain a big part of the variation of the mark-up ratios, over time. However, there is no evidence of non-linearity into this relationship.
Keywords: L13; C5; C13; 330; SMEs; Regulation; Mark up; Competition; Greece